Some features of Paleogen- Neogen deposits in the Song Lo depression and their relationship with tectonic activities - Huyên, Nguyễn Xuân; Pha, Phan Đông; Cường, Nguyễn Quốc; Anna, Wysoska (Vietnam Journal of Earth Sciences, 2018)
Paleogen- Neogen deposits in the Song Lo depression are continental and consist mainly of course grain size sediments: gravels, pebbles, brecia and course sand in the lower part and fine grain: sandstone, siltstone and argillite in the upper part. Sediment’s distribution in the time reflects their rhythm, that characterized for forming condition of braided, anastomosing and meandring rivers. In considering with activities of the Red fault zone, these sediments reflect a period of spreading and lowering with phases of reversing folding. The study area became stable and developed at the end of Neogen epoch.